(untitled) (Fiep Bulletin - online, 2011)
The development and improvement of physical fitness have been going at great speed, making the relevant figure of the trainer in football. Sports alternating moments of high intensity and short duration with moments of low intensity and long duration. Depending on their position and function tactic exercised in the field, an athlete may have a loss of up to 3 kg in a soccer match. The physical preparation of athletes is a vastly complex and among the variables to be controlled is the decrease in body weight and levels of dehydration during a soccer match. These variables can be indicators of fatigue, because they cause physiological changes marked. The hypothesis that levels of dehydration in professional athletes of the first and second division championship in Rio are relevant and that levels of dehydration reach values that interfere with the performance of athletes, the study aimed to determine whether there is a decrease in the percentage of body water athletes after the games, athletes by subdividing the position. The study was conducted with 26 professional players from Rio de Janeiro, aged 20 years and 34 years old, subdivided by five positions, the latter being the goalkeeper, defender, side, midfielders and attackers. For the proposed objective was achieved, was measured body weight of athletes before the start of the match and at the end and that’s calculated rate of sweating following the formula proposed by the ACSM (1996) (TS) = [(Pi - Pf ) x1000] / total time of physical activity. Concluding that the levels of dehydration in the Carioca championship in both the first division and second division are relevant and differ according to the tactical position of the athletes.